PELATIHAN MANUFAKTUR KOMPOSIT HASIL LIMBAH LAUT BAGI KELOMPOK PKK UNTUK MENINGKATKAN KETERAMPILAN WIRAUSAHA MANDIRI - Mardiansyah, Yopy; Rahman, Taufiq; Wibowo, Sadiq Ardo; Sapitri, Ria; Asmarawati, Citra Indah; Prasetiyo, Adi Bagus; Fahruddini, Reant Egie; Anggraini, Selly Putri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2024)
The Riau Islands region is one of the archipelago areas in Indonesia where most of the people depend on marine products, one of which is shellfish, which have various colors and beauty. In various regions, people have Using seashells to improve the quality of life. Shells can be used as building materials, collections, clothing, furniture decoration, and as souvenirs, both for functional purposes and interior decoration. The use of goods that are not economical but can produce high economic value is currently attracting the attention of craft market players. If made into crafts or souvenirs, seashells, which are a product of marine waste, can be very valuable. Various types of crafts are developing in today's society, one of which is crafts that use resin as the main material. The manufacturing process with this composite material can be carried out easily by all groups. This composite manufacturing training was given to the Family Welfare Empowerment (PKK) group in the Cipta Garden housing complex which is approximately 10 km from the ITEBA campus. This group actively gathers every month, but no productive activities are carried out. In principle, this activity provides knowledge and skills for this PKK group to be productive by producing various types of crafts with high selling value. So it is hoped that later it can become an idea for entrepreneurship